2015
DOI: 10.6007/ijarbss/v5-i1/1399
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Development in Festival Quality Management: Implications for Product Development and Marketing

Abstract: This paper seeks to explore the trends in the conceptual development of knowledge relevant in festival quality management. There is plethora of literature on festival quality that spans over three decades. However, researchers and practitioners have continued to grapple with trying to understand the why and what of festival quality study in special event tourism management. This taxonomical problem exist probably because of the historical antecedent of service quality research. This paper therefore provides mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to Parasuraman et al (1988), SQ is the gap between the service that customers anticipate from a service firm and their impression of the service that they receive. The components of fast food restaurants SQ have a significant positive relationship with PV (Carranza et al, 2018;Shahzadi et al, 2018), and the perceived value that is based on SQ may result in CS (Bassey, 2014). This is not unexpected given the well-established association between CS and RI (Yan et al, 2015), as well as PV (Yuksel & Yuksel, 2003).…”
Section: Literature Review Service Quality In Fast Food Restaurantsmentioning
confidence: 97%
See 2 more Smart Citations
“…According to Parasuraman et al (1988), SQ is the gap between the service that customers anticipate from a service firm and their impression of the service that they receive. The components of fast food restaurants SQ have a significant positive relationship with PV (Carranza et al, 2018;Shahzadi et al, 2018), and the perceived value that is based on SQ may result in CS (Bassey, 2014). This is not unexpected given the well-established association between CS and RI (Yan et al, 2015), as well as PV (Yuksel & Yuksel, 2003).…”
Section: Literature Review Service Quality In Fast Food Restaurantsmentioning
confidence: 97%
“…Previous research suggests that food quality (Ha & Jang, 2010), SQ (Ryu et al, 2012), and pricing fairness (Ryu & Han, 2010), all have a considerable beneficial effect on CS in the FFRs setting. According to Bassey (2014), perceived pricing fairness boosts CS and loyalty. In a similar vein, Kim et al (2013) confirmed the favorable link between perceived food healthiness and PV in the restaurant context.…”
Section: Perceived Value (Pv)mentioning
confidence: 99%
See 1 more Smart Citation